2021
DOI: 10.1002/jia2.25752
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and cost‐effectiveness of a family‐based economic empowerment intervention (Suubi + Adherence) on suppression of HIV viral loads among adolescents living with HIV: results from a Cluster Randomized Controlled Trial in southern Uganda

Abstract: Introduction Evidence from low‐resource settings indicates that economic insecurity is a major barrier to HIV treatment adherence. Economic empowerment (EE) interventions have the potential to improve adherence outcomes among adolescents living with HIV (ALWHIV) by mitigating the effects of poverty. This study aims to assess the efficacy and cost‐effectiveness of a savings‐led family‐based EE intervention, Suubi + Adherence, aimed at improving antiretroviral therapy (ART) adherence outcomes ALWHIV in Uganda. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Randomized and observational studies have demonstrated the potential for cash transfers to meaningfully rupture pathways from food insecurity and other material asset deprivations to HIV-related outcomes, including improved HIV self-management. [38][39][40] In evaluating the psychometric properties of the validated depressive symptom scale used in our study, we found that 1 symptom ("Little interest or pleasure in activities") was insubstantially correlated with other indicators of depression, resulting in its exclusion from the final EFA model. Among depressive symptoms, this one was endorsed most frequently (66%) by CALWH or their caregiver proxies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Randomized and observational studies have demonstrated the potential for cash transfers to meaningfully rupture pathways from food insecurity and other material asset deprivations to HIV-related outcomes, including improved HIV self-management. [38][39][40] In evaluating the psychometric properties of the validated depressive symptom scale used in our study, we found that 1 symptom ("Little interest or pleasure in activities") was insubstantially correlated with other indicators of depression, resulting in its exclusion from the final EFA model. Among depressive symptoms, this one was endorsed most frequently (66%) by CALWH or their caregiver proxies.…”
Section: Discussionmentioning
confidence: 81%
“…Randomized and observational studies have demonstrated the potential for cash transfers to meaningfully rupture pathways from food insecurity and other material asset deprivations to HIV-related outcomes, including improved HIV self-management. 38–40…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also shown the role of family-based empowerment in reducing the adverse effects of diseases and increasing the patients' quality of life, some of which are the studies by Tozan et al [ 59 ], Etemadifar et al [ 60 ], Davarpanah et al [ 48 ], and Hosseini et al [ 30 ]. It is worth mentioning that the family-centered empowerment model has been emphasized more in other chronic diseases [ 61 , 62 ] but could also be used in empowering breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from health clinics located in Rakai, Masaka, Lwengo, Lyantonde, Bukomasimbi, and Kalungu Districts—a region with high prevalence for HIV, compared to the national average (Uganda AIDS Commission, 2021). Details on participant recruitment and the intervention are provided in the study protocol (Ssewamala et al, 2019) and elsewhere (Ssewamala et al, 2020; Tozan et al, 2021).…”
Section: Methodsmentioning
confidence: 99%